The Gold Coast Review Vol. II. No. I. January-June 1926 - Government of Gold Coast (Government of Gold Coast, 1926)
It is not necessary for the Editor to say much in introducing the second issue of the Gold Coast Review. As mentioned in the introduction to Volume I., No. I., the Gold Coast Review is a half-yearly publication. Since the period represented by the first issue was the second half of the year 1925, the volume for that year consists of that one number only, and the present issue is the first of the two numbers for the year 1926 which will constitute volume II. It is with a feeling of great relief that we appear for the second time. Experience in the matter of publications on the Gold Coast has established the paradox that it is not so much Ie premier as Ie deuxieme pas qui coute. The first number was well received . The demand was good, though not so good as we hope it will become. The response to the appeal for contributions, as will be seen by the varied and interesting articles in this number. has been very encouraging. One grave defect remains. His Excellency the Governor, in congratulating the Editor on the start of the publication, expressed his regret at .. one blemish in a very useful list of contents--no con.. tribution from an African or non-Official European." Efforts have been made to remove this blemish . In addition to the appeals made in the Introduction to the first number for contributions from all sections of the community personal appeals have been made to several likely contributors outside official circles, and some of them have expressed their intention of sending in articles for future issues. We are glad to have a short article this time from the pen of the Honourable Mr. Casely Hayford. but all our other contributors are Government Officials. and the proportion from outside the Government service is thus not yet what we should like it to be. t the s me time there is cause for satisfaction in the wider range of interests represented in the present Issue.
Heritage
Keywords: Gold Coast; Review